FREQUENCY OF MALIGNANT CELLS IN SPUTUM CYTOLOGY OF TUBERCULOSIS SUSPECTED PATIENTS - Shah, Walayat (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
Background: Prolonged pulmonary inflammation may cause tissue damage and ge-nomic alterations. Furthermore, repair of tissue damage caused by tuberculosis can lead to pulmonary fibrosis and scarring. To find out the frequency of malignant cells on sputum cytology in suspected tuberculosis patients as it has been observed that all the chronic lung diseases along with tuberculosis raise the risk of lung cancer. Methodology: From March 2013 to September 2013, 100 patients with suspected tuberculosis were included in the study .Samples were mainly collected from out- door patients (OPD) laboratory at the Department of Pulmonology of Postgraduate Medical Institute, Lady Reading Hospital (PGMI-LRH) Peshawar. Both male and female of age 20 years or above with clinical and radiological suspicion were included in the study. Total of one hundred patients with age range 20 years to 70 years with mean age of 49 years were registered in this study. Out of these 100 patients, 59% were males and 41% females, and 47% belonged to urban area and 53% to rural area. Results: The most common symptom was fever, observed in 98% of patients. Cough, hemoptysis and weight loss was observed in 96 %, 80% and 45% respectively. Only 2% were smokers for more than 5 years. However no malignant cells were observed in any of these patients. Out of total 100 patients 88 were diagnosed as having tuberculosis by different investigations and 12 were with other causes including pneumonia, COPD and lung infections. Conclusion: Though chronic inflammation is one of the causative factors of lung cancer, and the major group of patients in our population pre-sented with tuberculosis but there were no malignant cells in their sputa on cytological examination to provide any clue of malignancy in these suspected patients of tuberculosis